2021
DOI: 10.1155/2021/3827991
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Adaptability of Dominant Plant Indigofera amblyantha Craib for Ecological Restoration of Rock Slopes in Stone Coal Mine

Abstract: The eco-restoration was a very effective measure to solve the problem of environmental pollution caused by the exposed mine surface in the stone coal mine site. In this study, the dominant plant, Indigofera amblyantha Craib, was well adapted to the eco-restoration in stone coal mining area. The changes of nutrient elements, pH, heavy metals in substrate material, the biological concentration/transfer factor, and the distribution and diversity of bacteria and fungi in rhizosphere soil were investigated. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
(75 reference statements)
1
0
0
Order By: Relevance
“…The soil pH and organic matter content are important indicators of soil quality [24,25]. The mobility and availability of heavy metals in soil were significantly affected by soil pH, which can control the adsorption-desorption and precipitation-dissolution of heavy metals in the soil [26,27]. The results revealed that the application of illite significantly raised the soil pH, which is consistent with findings of previous studies [28].…”
Section: Discussionsupporting
confidence: 88%
“…The soil pH and organic matter content are important indicators of soil quality [24,25]. The mobility and availability of heavy metals in soil were significantly affected by soil pH, which can control the adsorption-desorption and precipitation-dissolution of heavy metals in the soil [26,27]. The results revealed that the application of illite significantly raised the soil pH, which is consistent with findings of previous studies [28].…”
Section: Discussionsupporting
confidence: 88%